Withdrawal of disease-modifying antirheumatic drugs in patients with rheumatoid arthritis: a systematic review and meta-analysis. Issue 10 (17th February 2009) - O'Mahony, Rachel; Richards, Alison; Deighton, Chris; Scott, David
Abstract : Objective: To define the effects of withdrawing disease-modifying antirheumatic drug (DMARD) treatment from patients with established rheumatoid arthritis (RA) receiving stable, effective long-term DMARD treatment. Methods: A systematic literature search was conducted. Studies were included that were of high quality and enrolled adults with RA over 2 years' duration. A meta-analysis was performed on the number of disease flares in groups withdrawn from DMARD treatment compared with those who continued to receive DMARD. Results: The randomised controlled trial data were pooled into a meta-analysis and this showed that patients who withdrew from DMARD had a significantly worse risk of disease flare or deterioration than those who continued DMARD treatment. Conclusion: In patients who have their disease adequately controlled by DMARD and wish to reduce the dose or withdraw them, this should be done cautiously. Their disease activity should be monitored carefully so that they recommence DMARD therapy in the event of disease flare or deterioration.